The 2019 International Society of Hip Preservation (ISHA) physiotherapy agreement on assessment and treatment of femoroacetabular impingement syndrome (FAIS): an international consensus statement. Issue 4 (19th March 2021) - Takla, Amir; O'Donnell, John; Voight, Michael; Byrd, Thomas; Dienst, Michael; Martin, Rob Roy; Philippon, Marc J; Enseki, Keelan; Andrade, Tony; Safran, Marc; Christoforetti, John Joseph; Martin, Hal; et al.
Abstract: The 2019 International Society of Hip Preservation (ISHA) physiotherapy agreement on femoroacetabular impingement syndrome (FAIS) was intended to build an international physiotherapy consensus on the assessment, non-surgical physiotherapy treatment, pre-/post-operative management, and return to sport decisions for those patients with FAIS. The panel consisted of 11 physiotherapists and 8 orthopaedic surgeons. There is limited evidence regarding the use of physiotherapy in the overall management of those with FAIS. Therefore, a group of ISHA member physiotherapists, who treat large numbers of FAIS patients and have extensive experience in this area, constructed a consensus statement to guide physiotherapy-related decisions in the overall management of those with FAIS. The consensus was conducted using a modified Delphi technique. Six major topics were the focus of the consensus statement: (i) hip assessment, (ii) non-surgical physiotherapy management, (iii) pre-habilitation prior to hip arthroscopy, (iv) post-operative physiotherapy rehabilitation, (v) stages of post-operative rehabilitation and (vi) return to sports criteria/guidelines after surgery.